Upaya Peningkatan Kompetensi Guru SDN Kaliharjo dalam Mengintegrasikan Materi Moderasi Beragama pada Kurikulum Merdeka - Nur Rohmah Hayati (Prodi Pendidikan Agama Islam IAINU Kebumen, 2025)
This study aims to analyze the improvement of elementary school teachers’ competence in integrating religious moderation into the Merdeka Curriculum. The research employed a qualitative descriptive approach with a field research design conducted at SD Negeri Kaliharjo, Kaligesing District, Purworejo Regency. The research subjects consisted of ten elementary school teachers. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings indicate that teachers demonstrate improved understanding of religious moderation concepts and are able to integrate them into learning activities and the Project for Strengthening the Pancasila Student Profile (P5). The integration of religious moderation within the Merdeka Curriculum effectively strengthens character education and national values through contextual, reflective, and experiential learning. Improved teacher competence directly contributes to learning quality and the internalization of tolerance, diversity, and moderate religious attitudes among elementary school students